Dynamic surfaces for the study Of mesenchymal stem cell growth through adhesion regulation - Roberts, Jemma; Sahoo, Jugal; McNamara, Laura; Burgess, Karl; Yang, Jingli; Alakpa, Enateri; Anderson, Hilary; Hay, Jake; Turner, Lesley-Anne; Yarwood, Stephen; Zelzer, Mischa; Oreffo, Richard; et al. (American Chemical Society, 2016)
Out of their niche environment, adult stem cells, such as mesenchymal stem cells (MSCs), spontaneously differentiate. This makes both studying these important regenerative cells and growing large numbers of stem cells for clinical use challenging. Traditional cell culture techniques have fallen short of meeting this challenge, but materials science offers hope. In this study, we have used emerging rules of managing adhesion/cytoskeletal balance to prolong MSC cultures by fabricating controllable nanoscale cell interfaces using immobilized peptides that may be enzymatically activated to change their function. The surfaces can be altered (activated) at will to tip adhesion/cytoskeletal balance and initiate differentiation, hence better informing biological mechanisms of stem cell growth. Tools that are able to investigate the stem cell phenotype are important. While large phenotypical differences, such as the difference between an adipocyte and an osteoblast, are now better understood, the far more subtle differences between fibroblasts and MSCs are much harder to dissect. The development of technologies able to dynamically navigate small differences in adhesion are critical in the race to provide regenerative strategies using stem cells.